Method and system for extracting rare earth elements by high pulp density cracking
The extraction of rare earth elements from the solid feed through the high slurry density cracking step solves the problems of high cost of the existing rare earth element extraction process and poor metallurgical performance, and achieves efficient and economical rare earth element extraction effect.
Patent Information
- Application Number
- CN202380046001.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-13
- Filing Date
- 2023-06-13
- Publication Date
- 2025-02-14
AI Technical Summary
The existing rare earth element extraction process is costly and has poor metallurgical performance, and an efficient rare earth element extraction process is required to reduce capital expenditure and operational expenditure while maintaining or improving metallurgical performance.
The high slurry density cracking step extracts rare earth elements from the solid feed, including grinding the solid feed, mixing the solid feed with strong acid and water to form a slurry or slurry with high slurry density, and performing it in the reactor Cracking and finally leaching with an aqueous leaching solution to obtain a leaching solution containing rare earth elements.
This method significantly reduces capital expenditure and operational expenditure of the rare earth element extraction process, while improving metallurgical properties, enabling the leaching step to be completed in a shorter time without the need for high temperature leaching, and reducing the overall processing cost.
Smart Images

Figure BDA0005178117900000091 
Figure BDA0005178117900000092 
Figure BDA0005178117900000101
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 351,510, filed on June 13, 2022, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0002] The present invention belongs to the field of rare earth recovery. More specifically, the present invention relates to a method and system for recovering rare earth elements from solid feedstock through a high pulp density cracking step. Background Art
[0003] Rare earth elements (REEs) are a group of 17 elements that play an important role in modern society and are used in many high-tech and clean energy applications, such as permanent magnets for wind turbines, smartphone components, and rechargeable batteries for electric vehicles (Sadri, Nazari, & Ghahreman, 2017). In addition to the 15 lanthanide elements (lanthanum to lutetium), the group also includes scandium and yttrium.
[0004] The rare earth (RE) production industry has two main components: first, the extraction of REEs from ores; second, the separation of REE mixtures into individual compounds. The two main commercial methods for extracting REEs from ores are acid roasting or alkaline conversion (Demol and Senanayake, 2018). Since REEs are usually found together in minerals, the extraction step produces a mixture of REEs, and purifying them into individual element compounds is a complex and expensive operation due to their similar chemical properties.
[0005] Currently, the industry uses a multi-step extraction process with the following general scheme: decomposition → leaching → removal of impurities → conversion to useful or marketable products such as rare earth chlorides or rare earth oxides. Decomposition of rare earth ores can be achieved by various methods, all of which fall into the two categories mentioned earlier (i.e., acid roasting or alkaline conversion). One such method is a combination of sulfuric acid roasting and water leaching. The world's largest rare earth producer, in Bayan Obo, China, commercializes a sulfuric acid roasting process to process mixed bastnaesite / monazite concentrate (Demol and Senanayake, 2018). During the roasting process, the acid reacts with the ore to produce rare earth sulfates and monazite, two minerals that contain most of the world's rare earth elements (Qi, 2018, pp. 22, 56). In addition, impurities such as thorium, calcium, and iron are also converted to their sulfates.
[0006] After the acid roasting decomposition is complete, the sulfates are dissolved into the leachate and the remaining solids (containing silica, zircon and other undigested ore residues) are filtered out. The acid roasting process is referred to herein as "acid roasting water leaching" or ABWL process.
[0007] There remains a need for an efficient rare earth element extraction process that reduces capital expenditures and operating expenditures while maintaining or improving metallurgical properties.
[0008] The above information is information that the applicant believes may be relevant to the present invention, but this does not necessarily mean that the applicant admits (nor should it be interpreted as) that any of the above information constitutes prior art of the present invention. Summary of the invention
[0009] The object of the present application is to provide a method and system for extracting rare earth elements from solid feed by high pulp density cracking.
[0010] According to one aspect of the present application, there is provided a method for extracting rare earth elements from a solid feed, the method comprising: (a) grinding the solid feed; (b) mixing the ground solid feed with a strong acid and water to form a slurry or mud having a solid-liquid slurry density of at least 33%, and cracking the slurry or mud in a reactor at a temperature of about 30° C. to about 300° C. for about 30 minutes to about 6 hours; and (c) leaching the product of step (b) with an aqueous leaching solution to obtain a leachate containing rare earth elements. In some embodiments, cracking the slurry or mud in step (b) is a static step, and in other embodiments, the slurry or mud is stirred in the reactor during the cracking process in step (b).
[0011] According to one aspect of the present application, a method for extracting rare earth elements from a solid feed is provided, the method comprising: (a) grinding the solid feed; (b) mixing the ground solid feed with a strong acid and water to form a slurry having a solid-liquid slurry density of at least 33%, and stirring the slurry in a reactor at a temperature of about 30°C to about 300°C for about 30 minutes to about 6 hours; and (c) leaching the slurry with an aqueous leaching solution to obtain a leachate containing rare earth elements.
[0012] According to one embodiment, the strong acid is HNO3, HCl or H2SO4.
[0013] According to some embodiments, the cracking step (b) in the method uses a solid-liquid slurry density of about 33% to about 90%, or about 50% to about 80%, or about 65% to about 80%, or about 55% to about 75%, or about 70% to about 75%, and is carried out at a temperature (or temperature range) of about 30°C to about 200°C, or about 30°C to about 100°C.
[0014] In some embodiments, the aqueous leaching solution is water. Alternatively, the aqueous leaching solution may be an acidic solution poor in rare earth elements, such as may be obtained by other processes. In some embodiments, the leaching step is performed for about 1 hour to about 10 hours, or about 1 hour to about 5 hours, or about 2 hours to about 5 hours, or about 2.5 hours. In some embodiments, leaching is performed at a temperature (or temperature range) of about 20°C to about 100°C, about 20°C to about 90°C, about 20°C to about 50°C.
[0015] According to another aspect of the present application, a system for performing the above-mentioned method of extracting rare earth elements from solid feed is provided herein. The system comprises: (i) a grinding and / or milling device for grinding a solid feed to produce a ground solid feed; (ii) a cracking reactor having a ground solid feed ore inlet, a strong acid inlet, a water inlet and a mixed slurry outlet fluidly connected to the grinding and / or milling device, wherein the ground solid feed is received in the cracking reactor and mixed with a strong acid and water by an agitator arranged in the reactor to form a slurry having a solid-liquid slurry density of at least 33%; (iii) a device for heating the reactor to a temperature of about 70°C to about 300°C for about 30 minutes to about 6 hours; and (iv) a leaching device comprising a leaching chamber having a mixed slurry inlet, an aqueous leaching solution inlet and a leaching slurry outlet fluidly connected to the mixed slurry outlet of the reactor.
[0016] In some embodiments, the system further comprises means for heating the leaching chamber. Optionally, the system further comprises means for controlling one or both of the means for heating the cleavage reactor and the means for heating the leaching chamber. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] For a better understanding of the applications and other aspects and further features described herein, please refer to the following description in conjunction with the accompanying drawings, in which:
[0018] Figure 1 A is a high pulp density cracking water leaching process flow chart provided in one embodiment of the present application, Figure 1 B is a high pulp density cracking water leaching process flow chart of another embodiment of the present application;
[0019] Figure 2 is a schematic diagram of a high pulp density cracking leaching process according to one embodiment of the present invention, the process also comprising a downstream leaching step to further purify and process the obtained rare earth elements;
[0020] Figure 3 a sample particle size curve for the search mineral whole ore B (SMWB) sample; and
[0021] Figure 4 This is the grinding curve of the SMWB sample. DETAILED DESCRIPTION
[0022] definition
[0023] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0024] As used in the specification and claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.
[0025] The terms "comprising" and "including" as used herein should be understood as meaning that the recited elements or list is non-exhaustive and may or may not include any other additional suitable items, such as one or more further features, elements, components and / or ingredients, as appropriate.
[0026] In this specification, references to "one embodiment," "an embodiment," "another embodiment," "a specific embodiment," "a related embodiment," "an embodiment," "an additional embodiment," or "a further embodiment," or a combination thereof, mean that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment. Therefore, the foregoing phrases appearing in various places in this specification are not necessarily all referring to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in any suitable manner in one or more embodiments.
[0027] Unless otherwise indicated, all numbers expressing quantities of ingredients, properties such as temperatures and reaction conditions, and the like used in the specification and claims are to be understood in all instances as modified by the term "about". As used herein, the term "about" refers to numerical variations that may occur, for example, by typical measurements and liquid or solid handling procedures; by inadvertent or systematic errors in such procedures; by differences in the source, manufacture, or purity of ingredients used to make the compositions or perform the methods, and the like. The term "about" also includes amounts that differ due to different equilibrium conditions of the compositions resulting from a particular initial mixture or environment.
[0028] This article uses the following abbreviations: REE: Rare earth elements, including: lanthanides, scandium and yttrium LREE: Light rare earth elements, including: Lanthanum (La) Cerium (Ce) Praseodymium (Pr) Neodymium (Nd) Promethium (Pm) Samarium (Sm) Europium (Eu) and Gadolinium (Gd) Scandium (Sc) is often included in LREEs because it exhibits similar chemical behavior. HREE: Heavy rare earth elements, including: Terbium (Tb) Dysprosium (Dy) Holmium(Ho) Erbium (Er) Thulium(Tm) Ytterbium (Yb) Lutetium (Lu) Yttrium (Y) is often included in LREEs because it exhibits similar chemical behavior. TREE: Total rare earth elements
[0029] The present application provides a method and system for extracting rare earth elements from a solid feed, wherein cracking is performed at high temperature using a high pulp density. This is referred to herein as a "high pulp density cracking water leaching" or "HPDCWL" process. As used herein, the term "solid feed" refers to a solid containing rare earth elements, typically a concentrate or ore. The solid feed can be, for example, a concentrate, ore, or ore concentrate containing rare earth elements, however, it should be recognized that the process described herein can use any rare earth element-containing solid as a solid feed.
[0030] The HPDCWL process comprises the following steps: grinding a solid feed; mixing the ground solid feed with a strong acid and water to form a slurry or mud having a high solid slurry density; cracking the slurry or mud; and diluting the cracked slurry or mud with an aqueous leaching solution to obtain a leachate containing rare earth elements. Figure 1 A shows an example of the overall process, where cleavage can be performed with or without stirring. Each step of the process is described below.
[0031] Step 1: Grinding
[0032] The solid feed is first crushed and ground. Given enough time, the aggressive chemicals used for cracking can eventually penetrate many large particles, thereby maximizing the recovery of rare earth elements. However, for the HPDCWL process, the process duration must be within a reasonable range. The reaction rate of REE mineral conversion and REE dissolution is an important factor in the success of HPDCWL. Crushing and grinding large particles into finer particles can accelerate the cracking process.
[0033] Standard industry practice for leaching solid feed particles containing rare earth elements is to reduce the particle size to a level that allows the valuable minerals to be exposed to the aggressive chemicals. The optimum grinding target particle size can be obtained using a mineralogical approach involving measuring the particle size of the valuable minerals present in the solid feed. Alternatively, and more commonly, a battery of tests is performed with particle size as the target variable to determine the optimum particle size or size range.
[0034] In the embodiments of the present invention, the particle size or particle diameter of the rare earth solid feed is not particularly limited, and those skilled in the art can select it according to the actual needs of the specific situation. Select an appropriate grinding particle size or size range for this process to avoid over-grinding. In the high slurry density cracking step of the present invention, over-grinding may cause the formation of high viscosity mud, which reduces the efficiency of the cracking reaction. Grinding or grinding into very small particles will also consume too much energy and lead to an increase in co-dissolved impurities.
[0035] On the other hand, the study found that if the particle size or size range is too large, it is not conducive to the reaction between the solid feed and the acid. Specifically, insufficient grinding leads to larger particles, which can save some costs by reducing energy consumption in the grinding step, but also slows down the reaction rate, perhaps even to the point of preventing the reaction from completing in the cracking step.
[0036] A balance needs to be struck to select a particle size that is favorable for the solid-liquid reaction rate, but not too small to result in excessive cost and / or excessive co-dissolved impurities. It will be appreciated that the exact particle size range used in a particular HPDWL process can be optimized by a skilled artisan based on the requirements of each specific case.
[0037] In one embodiment of the HPDCWL process of the present application, a typical range of particle size is in the range of about 10 microns to about 4000 microns. In some embodiments, the particle size range is about 10 microns to about 1000 microns, or about 20 microns to about 200 microns. Similarly, the optimal particle size within this range can be selected for different situations by considering various criteria (including but not limited to mineral characteristics, operating costs, metallurgical properties, reaction rates of various species).
[0038] Step 2: Acid lysis
[0039] The next step in the HPDCWL process involves mixing the ground solid feed with a strong acid and water to create a slurry or mud, followed by heating for a period of time, which can be done with or without stirring. The amount of acid and water used in this step is kept to a minimum, but levels that do not cause significant material handling or mixing difficulties can be used.
[0040] For example, when processing Canadian ore, the crushed and ground ore is mixed with a small amount of strong acid and the resulting paste is then diluted by adding a small amount of water to form a slurry or mud with a high pulp density.
[0041] The term "slurry" as used herein refers to a flowable suspension of small particles in a liquid. The term "mud" as used herein refers to a mixture of water or an aqueous solution and small or fine particles. The viscosity of a mud is higher than that of a slurry.
[0042] In the HPDCWL process, the high pulp density mixture formed by mixing the ground solid feed with a strong acid and water (or aqueous solution) will initially be a slurry or mud, depending on the amount of acid and water added and the amount of solids. However, it has been observed that at high temperatures, the chemical reaction between the added acid and the silicate minerals in the ground feed will rapidly increase the viscosity of the slurry, causing the mixture to become a mud or behave like a mud. This may occur in the initial stages of the cracking step. The pulp density is determined by calculation based on the mass of solids and liquids in the mixture. However, since water and acid are quickly adsorbed by and react with solid ore particles after addition, the calculated pulp density does not reflect the actual state of the mixture. Therefore, the calculated pulp density can be considered as the "nominal" pulp density referred to herein.
[0043] In some embodiments of the HPDCWL process, conversion of the slurry to a mud is avoided, for example, by diluting the mud with sufficient additional water or aqueous solution so that the mixture retains or restores the properties of a slurry. In this embodiment, care is taken to avoid adding too much water or aqueous solution; if the mixture is diluted too much, the pulp density and the acidity of the slurry will be reduced to a level that is detrimental to the reaction rate.
[0044] Whether the high pulp density mixture will be a slurry or a mud, or whether it will transition between the two, will also depend largely on the mineralogical reactions under the cracking conditions.
[0045] In general, in the acid cracking step of the HPDCWL process of the present application: (i) a high pulp density is maintained; (ii) the amount of acid and water or aqueous solution is selected to optimize the overall metallurgical properties; and, optionally, (iii) the viscosity of the mixture is maintained within a certain range to allow the slurry or mud to be stirred. When a viscous mud is formed and adheres to the reactor so that it hardens and becomes static, (iii) is not satisfied, which is unfavorable for the effectiveness or high efficiency of the cracking reaction using stirring during the cracking process. However, as shown herein, stirring is not necessary for effective or efficient cracking.
[0046] The acid used in the cleavage step is a strong acid, such as sulfuric acid (H2SO4), nitric acid (HNO3) or hydrochloric acid (HCl). In some embodiments, a mixture of two or more strong acids is used in this step.
[0047] The acid can be added in its most concentrated form or in a diluted form. The final concentration of the acid in the cracking step depends on the acid used, however, in some embodiments, the concentration can be from 100% to about 50%. The actual minimum concentration of the acid used in this step depends on the nominal pulp density and the optimal acidity optimized in the HPDCWL cracking and leaching steps. Conventional ABWL requires very pure and concentrated acid to operate properly. In contrast, in HPDCWL, the presence of water in the acid is not a problem and can also help improve metallurgical properties.
[0048] As used herein, the term "high pulp density" refers to a solid pulp density in a slurry or mud of at least about 33%. In some embodiments, the method is performed using a solid pulp density of about 33% to about 90%, or about 50% to about 80%, or about 65% to about 80%, or about 55% to about 75%, or about 70% to about 75%. In conventional leaching operations, the pulp density is 20%, and in REE leaching it is at most 10%.
[0049] The high density slurry / mud is heated to a temperature of about 30°C to about 300°C, or about 30°C to about 200°C, or about 30°C to about 100°C. In one embodiment, the upper limit of the temperature is the boiling point of the aqueous component of the slurry or mud in the reactor. By maintaining the temperature below the boiling point, water loss due to evaporation can be minimized. In an alternative embodiment, the high density slurry is heated in an autoclave reactor to a temperature between the boiling point of water and 300°C using a temperature above the boiling point of the aqueous component.
[0050] Then, the slurry or mud is reacted in a reactor or autoclave for 30 minutes to 24 hours (with or without stirring). For example, the reaction is carried out for about 30 minutes to about 18 hours, or about 30 minutes to about 12 hours, or about 30 minutes to about 6 hours, or about 30 minutes to about 5 hours, or about 1 hour to about 4 hours. In this step, stirring can be selected to accelerate the reaction. In addition, using an agitator in this step helps to maintain the uniformity of the slurry or mud, and prevents the formation of concentration and temperature gradients. However, no stirring is required in the cracking process.
[0051] In the cracking step, when stirring is used, the ground rare earth solid feed in the slurry can be quickly forced to mix with the strong acid through stirring, so that the solid feed containing rare earth is fully infiltrated by the strong acid, avoiding subsequent agglomeration and providing favorable conditions for the cracking reaction.
[0052] In some embodiments, the cleavage step can be performed without stirring. The static HDPCWL process is referred to herein as the SHDPCWL process, which is a subset of the HDPCWL process. Therefore, unless otherwise stated, any reference to the HDPCWL process includes the SHDPCWL process. In embodiments of such static processes, the cleavage time is from about 30 minutes to about 18 hours, or from about 30 minutes to about 12 hours, or from about 30 minutes to about 6 hours, or from about 1 hour to about 6 hours, or from about 2 hours to about 6 hours.
[0053] It was found that the pyrolysis efficiency is improved when the solid residue after pyrolysis is drier and less wet. This is particularly evident in static processes, where the longer the pyrolysis time and the drier the pyrolysis solid residue, the higher the REE recovery.
[0054] The process parameters described above and exemplified in the examples are intended to maintain the amount of acid in concentrated form, thereby increasing the mineral decomposition rate. In some embodiments, increasing the amount of acid added during the cracking process can increase or maximize the rare earth element value in the subsequent leaching step.
[0055] Step 3: Leaching
[0056] After the cracking step, the dissolved rare earth elements are removed from the solid feed by leaching, in particular water leaching. Leaching can be performed, for example, by heap leaching, tank leaching or barrel leaching (e.g., with stirring). The aqueous leaching solution is water or an acidic solution depleted in rare earth elements (e.g., recovered from other process steps).
[0057] The leaching step can be performed as follows: - adding an aqueous leach solution to the slurry or mud from the cracking step and optionally allowing the mixture to solidify for a period of time; and - a heap leaching step is carried out over a period of time, wherein the leach solution is passed through the slurry or mud (with or without the above-mentioned solidification step) at a slow flow rate to promote a long and slow reaction; or - An agitated leaching step is performed, wherein the slurry or mud from the cracking step (with or without the above-mentioned solidification step) is stirred with the aqueous leach solution in a tank or drum for a period of time to promote a rapid reaction.
[0058] First, water or an aqueous solution (e.g., an aqueous solution recovered from other operations) is added to the slurry to improve the efficiency of leaching. The slurry or mud in step 2 is slowly diluted to reduce the solid-liquid pulp density to less than about 50%. Sudden dilution of acidity by adding too much water in a short period of time should be avoided to prevent local over-dilution and precipitation of rare earth elements. Specifically, the slurry or mud in step 2 is diluted by gradually or gradually adding water to achieve the pulp density required for leaching, rather than immediately and quickly diluting by adding a large amount of water at one time.
[0059] As described herein, the solid pulp density in the leaching step is calculated based on the mass of solid feed introduced in the cracking step and the amount of water or aqueous leach solution added to the residue produced in the cracking step. Any solid mass changes that occur in the cracking step are not taken into account when calculating the solid pulp density in the leaching step.
[0060] The higher the solid slurry density, the less fresh water needs to be added during the leaching step. With this HPDCWL process, it is possible to successfully operate at much higher slurry densities during the leaching process than with the conventional ABWL process. When selecting the appropriate leaching slurry density, the highest possible concentration should be selected without compromising the rare earth element recovery rate.
[0061] In the conventional process, about 10 parts by mass (g) of water are required for every 1 part (g) of solid feed, which corresponds to a solid-liquid slurry density of about 9%. Although this slurry density can be used in the present HPDCWL process, it is not necessary to reduce the slurry density to such a low level. On the contrary, using a slurry density within the above range but above 9% will not significantly affect the rare earth element recovery rate of leaching. Compared with the conventional process, the use of a higher leaching slurry density can significantly reduce the capital expenditure and operating expenditure of the entire rare earth element recovery process.
[0062] Leaching is carried out at a temperature that is conducive to or improves the efficiency of leaching. For example, the water immersion temperature can be ambient temperature, standard room temperature, or an elevated temperature. For example, during the leaching process, the temperature of the slurry can be maintained at a higher level (e.g., about 70°C to about 100°C), which requires heating. However, such heating is not necessary. On the contrary, in some embodiments, the temperature of the leaching process can be reduced by simply removing the heating source and allowing the remaining heat in the cracking step to be naturally released into the environment without providing additional heating. In this embodiment, the temperature range of the leaching process can be changed from the temperature used in the cracking step to ambient temperature (depending on environmental conditions).
[0063] In other embodiments, the temperature of the leaching process is maintained in the range of about 20°C to about 100°C, such as about 20°C to about 90°C, about 20°C to about 50°C, about 25°C, or about 50°C.
[0064] In conventional leaching processes (such as that used by ABWL), in order to obtain good rare earth element recovery, it is necessary to maintain a relatively high temperature (e.g., 90°C) during the leaching process. However, with the present HPDCWL process, the leaching temperature can be much lower without negatively affecting rare earth element recovery.
[0065] Conventional processes (such as those used by ABWL) also require a long leaching step to completely dissolve the rare earth elements (up to 36 hours). In contrast, the leaching step used by the present HPDCWL process can be completed in a shorter time. Therefore, the leaching step can be performed for about 1 hour or about 2 hours. In some embodiments, the leaching time is from about 1 hour to about 20 hours, or from about 1 hour to about 10 hours, or from about 1 hour to about 5 hours, or from about 2 hours to about 5 hours, or about 2.5 hours or about 3 hours.
[0066] According to other embodiments, water leaching is performed by a process comprising washing the slurry or mud from the cracking step and collecting the water wash. The water temperature for water washing ranges from about 20°C to about 100°C, such as about 20°C to about 90°C, about 20°C to about 50°C, about 25°C, or about 50°C.
[0067] In this embodiment, each washing stage uses water or an acidic solution poor in rare earth elements, which can be, for example, a solution recycled from another operation step. The washing volume can vary greatly depending on the washing method.
[0068] CCD (Counter Current Decantation) is a classic washing process used in industry to obtain the best washing performance.
[0069] Finally, the rare earth element product extracted in the leaching step can be processed according to standard techniques to purify the rare earth elements as required by downstream applications. A variety of downstream processing technologies can be applied and are not limited by the present HPDWL process.
[0070] In a specific non-limiting embodiment, the rare earth element leaching product is processed by direct oxalate precipitation, such as Figure 2 As shown. In the direct oxalate precipitation method, a rare earth element precipitate is obtained from the acidic composition produced by the leaching step by adding a reducing agent to the acidic composition, wherein the pH of the acidic composition is 0.5 to 3 or the pH is adjusted to 0.5 to 3 with an alkaline agent, and then the oxalate is directly added to the composition containing the reducing agent. This forms a REE oxalate precipitate in the mixture, which can be removed by solid-liquid separation. The resulting REE oxalate can then be washed and further processed into marketable REEs or REE salts. This downstream process is referred to herein as the direct oxalate precipitation method because the oxalate is added directly to the acidic composition containing the reducing agent without the need for a prior purification or precipitation step as required by traditional REE recovery processes.
[0071] The present invention also provides a system for implementing HPDCWL. The system includes: a grinding and / or milling device for grinding a rare earth-containing solid feed to produce a ground solid feed (or a rare earth ore concentrate); a reactor having a solid feed inlet, a strong acid inlet, a water inlet, and a mixed slurry outlet fluidly connected to the grinding and / or milling device, wherein an agitator is arranged in the reactor; a device for heating the reactor; and a leaching device having a leaching chamber, the leaching chamber having a mixed slurry inlet fluidly connected to the mixed slurry outlet of the reactor, an aqueous leaching solution inlet, and a leached slurry outlet.
[0072] Optionally, the system also includes means for controlling various aspects of the HPDCWL process, such as heating of the cleavage reactor and / or the leaching chamber. In addition, in some embodiments, it may be useful to monitor the slurry during the cleavage reaction and, depending on the state of the slurry, add additional water or aqueous solution to the cleavage reaction through a water inlet. This may be performed manually or automatically by incorporating additional control components (e.g., computerized sensors and control components) into the system.
[0073] The components of the system for performing the HPDCWL process can be standard components similar to those used in the conventional ABWL process. Typically, the cracking reactor is an open reactor with some form of cover or lid to minimize water loss during the cracking reaction. The reactor can include any effective stirring device, such as those well known in the art. However, it should be recognized that to successfully mix the viscous, high temperature, low liquid ratio, high viscosity, high acidity slurry produced in the HPDCWL process, a fairly strong stirring is required to avoid the slurry from forming a paste or cement mixture before solidification. In addition, a suitable stirring / agitation device should be selected to avoid any solidified slurry from accumulating along the reactor wall. A non-limiting example of such a stirring or agitating reactor is a cement truck-type mixing device that can withstand high temperatures and high acidity.
[0074] The agitator in the reactor is configured to be turned on and off as needed. For example, in the SHDPCWL process, the agitator is used only to mix the components of the initial slurry or mud to be cracked, and then turned off to allow the cracking to continue under static conditions.
[0075] Figure 2 An example of a system suitable for performing the present HPDCWL process is schematically depicted. It should be understood that the components of the system may vary depending on site requirements, availability and / or cost considerations.
[0076] In order to better understand the invention described herein, some embodiments are described below. It should be understood that these embodiments are only for illustrative purposes. Therefore, they should not limit the scope of the present invention in any way. Example
[0077] Example 1: Changes in process conditions for high slurry density cracking water leaching under stirring
[0078] The sample used in this study is a crushed whole ore sample, which is used as solid feed with a particle size of 6 mesh. The TREE grade of the ore is 1.05%, and rare earths are mainly found in allanite and yttrium niobium ore.
[0079] Figure 1 B provides a conceptual flow diagram of the high pulp density cracking water leaching process according to the embodiment of this example study. In this HPDCWL study, all feed samples were ground to P 80 (i.e. the particle size at which 80% of the material passes when sieved) is 121 microns. The ground solid feed is then mixed with acid and a small amount of water in a smaller reactor (ore cracking reactor), usually forming a viscous paste mixture. The stirring of the paste is carried out by a stirrer, which is designed to maximize the stirring effect. The ore cracking reactor is placed in a heating kettle to provide a stable temperature for the paste in the reactor. The cracking duration is 4 hours. Subsequently, the "cracked" sample is transferred to a larger reactor (leaching reactor) in the form of a paste, and deionized (DI) water is added to reduce the pulp density (leaching pulp density). The pulp is stirred at a speed of 250 rpm using a conventional stirrer and leached for 2.5 hours. After leaching, the pulp is filtered and washed to obtain solid and liquid samples for chemical analysis.
[0080] The purpose of the cracking tests was to ensure effective and adequate stirring of the high pulp density paste. Some standard agitators used in leaching reactions were tested in the first few trials, but without success. It was found that a 3D printed agitator with a diameter close to the reactor size could provide better stirring of the paste. However, other agitators could also be used.
[0081] result
[0082] During this study, certain conditions were changed to maximize the recovery of the HPDCWL process, namely, grinding the feed; high temperature (90°C) in the cracking process, high pulp density, high acidity (but the same acid dosage). These findings are discussed below.
[0083] Effect of grinding
[0084] In the first study, 4 min grinding (P 80The effect of grinding the sample was compared to the ungrinded test. As shown in Table 1, the ungrinded 4-hour pyrolysis and 2.5-hour leaching test (baseline) recovered 64.6% of the TREEs. The same test on the ground sample successfully increased the TREE recovery to 72.1%. The LREE, HREE, Dy, and Nd recoveries in the 4-minute grinding test were all higher than the baseline test. Table 1: Effect of grinding on high pulp density cracking water leaching process Unless otherwise stated, percentages are by weight.
[0085] Effect of leaching temperature
[0086] Two tests were compared using different leaching temperatures (25°C and 90°C). As shown in Table 2, the final TREE recovery remained unchanged, indicating that increasing the leaching temperature is not necessary for the high pulp density cracking water leaching process. Table 2: Effect of leaching temperature on high pulp density cracking water leaching process
[0087] Effect of pyrolysis temperature
[0088] When lower temperatures were tested at the pyrolysis stage (rather than the leaching stage), very different metal recoveries were achieved. As shown in Table 3, at 90°C the pyrolysis process was very efficient, achieving a TREE recovery of 72.7%. However, at the lower temperature of 50°C, pyrolysis leaching only recovered 51% of the TREEs. Table 3: Effect of pyrolysis temperature on leaching of high pulp density pyrolysis water
[0089] Effect of adding impurity ions
[0090] The addition of the two impurity ions at the beginning of the cracking stage was examined. As shown in Table 4, the addition of Mg and Mn ions did not significantly improve the recoveries of TREE, Dy, and Nd. Table 4: Effect of adding two impurity ions in the cracking stage on the leaching of high pulp density cracking water *Sulfate based
[0091] Effect of pyrolysis pulp density
[0092] To investigate the effect of pyrolysis pulp density, three larger batch tests were conducted, all using 300 g samples. The nominal pulp density at the pyrolysis stage did not appear to have a significant effect on TREE recovery (Table 5). TREE recoveries were 72.3%, 72.4%, and 70.1% when pulp densities were 58%, 71%, and 75%, respectively. Table 5: Effect of nominal pulp density at the cracking stage on water leaching from high pulp density cracking
[0093] Effect of acid type
[0094] Finally, three 300 g batch tests were conducted to compare the use of different types of acid in a high pulp density cracking water leaching process. Each acid dose provided the same H + Concentrations, using HNO3 and HCl appear to recover more TREEs than H2SO4 (Table 6). When using H2SO4, the process leached 72.4% of TREEs. When using HCl, 75.5% of TREEs were recovered. Using HNO3 resulted in a TREE recovery of 79.9%. Table 6: Effect of acid type on high pulp density cracking water leaching
[0095] Effect of leaching slurry density
[0096] The 100 g batch tests (Tables 1 to 4) conducted in this study were leached at a pulp density of 9.1%; the 300 g batch tests (Tables 5 and 6) were leached at a pulp density of 20%. Due to the different test batches, direct comparison of the results is not appropriate. However, considering that the higher leaching pulp density in the 300 g test had no significant effect on the rare earth element recovery, the results demonstrate the feasibility of increasing the leaching pulp density in the HPDCWL process without negative effects. Higher leaching pulp density can significantly reduce the capital expenditure (Capex) and operating expenditure (Opex) of the leaching process.
[0097] This study targeted Canadian REE whole ore as a solid feed sample, with the main elements being Nd (in allantite) and Dy (in yttrium niobate). Without grinding, the conventional ABWL process recovered 71% of TREE at the same acid dosage (150 kg / t). As shown above, 72.4% of TREE was recovered by the HPDCWL process using sulfuric acid. When HCl or HNO3 was used, the recoveries increased to 75.5% and 79.9%, respectively.
[0098] To reduce the cracking reaction time from weeks to hours, the HPDCWL process relies on the use of ground samples as feed. The process avoids the rotary kiln operation in ABWL, significantly reducing operating expenses (Opex) and capital expenditures (Capex). The HPDCWL process is carried out at high slurry density and moderate temperature. Compared with ABWL, both leaching time and leaching temperature are significantly reduced, significantly reducing overall processing costs. By using less water (20% slurry density vs. 9.1%), it was found that higher leaching slurry density did not affect the recovery of TREE. The HPDCWL process can be further optimized in many aspects. Both engineering design and metallurgical control can be adapted to specific circumstances to optimize the efficiency and economy of the HPDCWL process.
[0099] To compare with the results obtained using the above changes in the HPDCWL process, the same all-solids feed sample was subjected to a conventional ABWL process and 71% TREE recovery was achieved.
[0100] Overall, these results suggest that the high pulp density cracking water leaching process is an effective and economically attractive alternative to the standard acid roasting process.
[0101] Example 2: Changes in process conditions for high slurry density cracking water leaching without stirring
[0102] The purpose of this example was to demonstrate the role of agitation in the pyrolysis step and to optimize the pyrolysis conditions in static (ie no agitation) high pulp density pyrolysis water leaching (SHPDACWL).
[0103] The study was conducted using a batch of crushed whole ore samples (Search Mineral Whole Ore B, SMWB). The samples were crushed to 10 mesh and then divided into 1 kg batches. The particle size analysis of the crushed ore was as follows Figure 3 Although most of the work was performed on raw samples as received, some testing was performed on SMWB ground samples, with the grinding curves shown in Figure 4 shown.
[0104] Table 7 provides a summary of the mineralogical analysis of the whole ore of typical search minerals. The main elements of the ore are neodymium (Nd) and dysprosium (Dy). Nd is mainly found in allantite (accounting for 92.82% of Nd), and Dy is mainly found in yttrium columbite (accounting for 88.96% of Dy). SWMB elemental analysis shows that the ore contains 0.340% cerium (Ce), 0.020% dysprosium (Dy), 0.143% neodymium (Nd) and 7.42% iron (Fe). Table 7: Mineralogical analysis of the whole ore of the search mineral
[0105] Figure 1 A schematically depicts a conceptual flow chart of the high pulp density acidic cracking water leaching process used in this example, wherein the cracking step is performed under static conditions (i.e., without stirring). For the HPDACWL test work, all feed samples were ground to P 80 is 121 microns. The ground feed solids are then mixed with acid and a small amount of water in a smaller reactor (ore cracking reactor), usually forming a viscous, paste-like mixture. The ore cracking reactor is placed in a heating kettle to provide a stable temperature for the paste in the reactor. The cracking duration is 4 hours. After cracking, the "cracked" sample (wet paste or dry paste) is transferred to a larger reactor (leaching reactor) and deionized (DI) water is added to reduce the pulp density (leaching pulp density). The pulp is stirred at 250 rpm using a conventional agitator and leached for 2.5 hours. After leaching, the pulp is filtered, washed, and dried to obtain solid and liquid samples for chemical analysis.
[0106] Both ASWL and ABWL processes were performed on the same whole ore sample with a total rare earth element TREE recovery of 81%.
[0107] Using HPDCWL, for example as described in Example 1, the slurry or paste employed in the cracking step has high viscosity and high acidity and is maintained at high temperature during the cracking process. The high viscosity, acidity and temperature in the reactor together mean that the agitator used in the cracking step may face engineering challenges, especially material corrosion. However, if there is no significant agitation during the cracking process, corrosion will be greatly reduced.
[0108] In this example, the HPDCWL process was performed without agitation during the cleavage step, but under static conditions. Other conditions were evaluated using static cleavage conditions, as described below.
[0109] result
[0110] Effect of Slurry Density on the Cracking Process
[0111] Table 8 summarizes the effect of adding water when using the SHPDACWL process. It was found that when less water was added, the overall metal recovery was the lowest in the group (e.g., TREE recovery was 77.3%). When the amount of water added was doubled or tripled, the metallurgical recoveries of both Nd and Dy were improved, resulting in higher TREE recoveries (e.g., >= 81.9% TREE). However, when the amount of water added reached 5 mL, the nominal pulp density dropped to 61%, the beneficial effect of adding water did not increase, and the recovery also dropped from the maximum value. The concept of nominal pulp density is adopted in this paper to reflect the fact that the mixture of ground ore, acid and water initially appears as a wet paste and then becomes a completely dry solid block at the end of the cracking process. However, when water is added before the water leaching step, the dry block is easily softened and converted into a slurry. Using the concept of nominal pulp density means that the mixture during the cracking process is a wet paste or a "dry" block. Even if water is added during the cracking process, no real slurry is observed. Table 8: Effect of adding water to SHPDCWL
[0112] Effect of acid addition during pyrolysis
[0113] As shown in Table 9, adding more acid (300 kg sulfuric acid per ton of ore) in the cracking step of SHPDCWL significantly improved metal recovery. TREE recovery and Nd recovery increased by nearly 10%. Dy recovery increased from 64.7% to 79.4%. The significant correlation between Nd / Dy recovery and total acid dosage suggests that the lack of sufficient acid in the cracking and / or leaching steps is the limiting factor for REE recovery. Table 9: Effect of acid dosage in SHPDCWL
[0114] Effect of lysis duration Table 10 provides data illustrating the impact of a longer cracking duration (18 hours) in SHPDCWL. The results show that extending the cracking step to 18 hours instead of 4 hours did not result in any improvement in metallurgical recovery. Considering that extended cracking times at high temperatures result in higher costs, there is no need to obtain improved metallurgical results by extending the cracking time. This result can be explained by the observation that all wet pastes tested turned into dry chunks in less than 4 hours. The dry state of the mixture would result in a very slow reaction or even a complete stop. Table 10: Effect of lysis duration in SHPDCWL
[0115] Effect of leaching duration
[0116] The data presented in Table 11 compare the results of REE recovery using different leaching durations using the SHPDCWL process. The total amount of rare earths extracted was similar for leaching times of 1.5 and 2.5 hours. However, the recovery of Dy increased significantly when the duration was extended from 1.5 to 2.5 hours. Further doubling of the leaching time to 5 hours did not produce any benefit in REE recovery. Table 11: Effect of leaching duration
[0117] Effect of leaching temperature
[0118] The data provided in Table 12 show the effect of leaching temperature in the SHPDCWL process, which indicates that higher temperature is not an important factor affecting Nd recovery, but is beneficial to the dissolution of Dy. At 90 °C, the leaching rate of Dy was 64.7%, while when leaching was carried out at an ambient temperature of 25 °C, the Dy recovery was only 57.4%. Table 12: Effect of leaching temperature
[0119] The results of the above studies are summarized in Tables 7 to 12. The results show that for the target ore samples used, stirring is not required in the pyrolysis step of the HPDCWL process. Pyrolysis of REE-containing minerals can be achieved in a relatively short time (4 hours) at moderately elevated temperatures (50-90°C).
[0120] To further confirm these results, similar studies were conducted using larger ore samples. In subsequent studies, tests were performed at a 100g or 1kg scale to help identify any factors hidden in the test scale.
[0121] Effect of leaching slurry density (larger scale)
[0122] A major cost of rare earth element cracking and leaching is the large consumption of water and the potential for associated pollution. In the traditional ABWL process, the water-ore ratio is maintained at 10:1 to maximize the dissolution of rare earth elements. However, the target ore used as feedstock in this study is a low-grade whole ore. Therefore, it is speculated that not so much water is needed to fully recover the cracked REE minerals. In this set of experiments (Table 13), the leaching slurry density was increased from the original 16.7% to 20% and 25%, indicating that the fresh water usage was reduced from 5.0 tons / ton of ore to 4.0 tons / ton of ore and 3.0 tons / ton of ore. The metal recovery results show that reducing the amount of water added by 25% in the leaching step does not reduce the metal recovery rate. In fact, the recovery rates of both Dy and Nd are higher. For the same amount of acid residue in the cracked solids, the less water added, the higher the pH value, which can provide slightly better thermodynamic conditions for rare earth element dissolution. In this case, we saved 25% of fresh water without sacrificing the recovery rate of rare earth elements. When the water addition was reduced by 40% and the leaching slurry density was increased to 25%, the recoveries of both Nd and Dy decreased significantly, indicating that the solubility of rare earth elements under this acidic condition became the limiting factor for the dissolution of rare earth elements. The highest REE recovery was observed at a leaching slurry density of 14.3%, indicating that adding more water to the leachate facilitated REE dissolution. However, from 20% to 14.3%, the REE recovery increased by only 3%, requiring the addition of an additional 50% of fresh water. Therefore, it may be sufficient to use a higher slurry density depending on the specific situation; as will be readily appreciated by those skilled in the art, economic calculations can be performed on a case-by-case basis to determine the optimal slurry density in the leaching step. Table 13: Effect of leaching slurry density (100 g ore)
[0123] Effect of acid dosage
[0124] As shown in Table 14, the effect of acid dosage on rare earth element recovery was verified at a larger scale (i.e., 100 g). By increasing the acid dosage from 150 kg per ton to 400 kg per ton, TREE recovery increased by nearly 10%. Both Nd and Dy recoveries were significantly improved. Table 14: Effect of acid dosage (100 g ore)
[0125] Effect of pyrolysis pulp density
[0126] As shown in Table 15, the effect of water addition in static high pulp density cracking varies when more ore is used. In the smaller scale tests (10 grams), water addition significantly increased the recovery of rare earth elements at the end of leaching (see above). However, in the 100 g scale test, TREE recovery decreased with the increase in water addition. At zero water addition (only acid addition affects pulp density), 86.1% of TREEs were dissolved. When 400 kg of water per ton of ore was added, corresponding to a nominal pulp density of 59%, the recovery decreased to 57.7%.
[0127] It was observed that during the small scale tests (10 g), all solids appeared to be dry at the end of the cleavage step. However, in the 100 g scale tests, all cleavage residues remained as a wet paste. This difference in the properties of the solid residues after cleavage suggests that a portion of the water in the 100 g test remained in the solid residue as free water due to the increased thickness of the solid paste in the cleavage reactor. Table 15: Effect of pyrolysis pulp density (100 g ore)
[0128] Effect of lysis duration
[0129] As shown in the data provided in Table 16, the effect of duration of cracking at a larger scale is similar to the trend observed in the small-scale study. By extending the cracking duration from 2 hours to 6 hours, the recoveries of TREE, Dy and Nd are significantly improved. Observations using 100 g of ore show that at 2 hours and 4 hours, the cracked solids are still in a wet paste state. However, after 6 hours of cracking, the solid residue appears to be much drier. Table 16: Effect of cracking duration (100 g ore)
[0130] Effect of leaching temperature
[0131] The results provided in Table 17 summarize the effects of different leaching temperatures at a 100 g ore scale. The results show that Dy and Nd recoveries can be higher at lower leaching temperatures. At 25°C, the recovery of TREE was 89.7%. Increasing the temperature to 75°C resulted in a decrease in metal recovery of approximately 4%. This is significantly different from observations for this ore using current industrial conditions, where 90°C is considered necessary to maximize TREE recovery after ABWL. Without wishing to be bound by theory, the fact that high temperatures are not required in the SHPDCWL process suggests that the degree of cracking that occurs in the SHPDCWL process is higher than in the conventional ABWL process. Therefore, there is no need to continue cracking the minerals that lock in the rare earth element values during the leaching step. Therefore, it is unnecessary to use higher temperatures to accelerate the reactions in the leaching step. Table 17: Effect of leaching temperature (100 g ore)
[0132] Following the above studies, the SHDPCWL process was further scaled up from 100g to 1kg in the cracking step. Again, when the scale was scaled up, the cracking solids looked very different due to experimental design and equipment limitations. At the 10g scale, the process produced completely dry solids after cracking at 95°C for 4 hours, while at the 100g and 1kg scales, the solid residue after cracking looked much wetter. The degree of dryness during the cracking process is considered to be a hidden factor in the process. The results of this set of tests showed that higher TREE / Nd / Dy recoveries can be achieved at a smaller scale using dry cracking solids. When the scale was scaled up, the cracking solids were still wet, which changed the reaction mechanism and led to a decrease in rare earth element recovery. This conclusion was further supported by the results of the cracking time study, where the longer the duration of the cracking step, the solids produced were much drier than those obtained using a shorter cracking step, and also resulted in more rare earth elements being leached at the end of the leaching step.
[0133] By determining the improvements provided by the dry residue produced by pyrolysis in the SHPDCWL process, it is possible to use the process to maximize TREE recovery; specifically, by controlling the degree of dryness during pyrolysis. Such control may include one or more of the following: - Quantitative monitoring of the dryness of pyrolysis solids during the process. - Prolonging the duration of the lysis step so that the solid residue at the end of the lysis is dry. - Adjust the amount of water added during the lysis step to avoid a wet residue. - Provide an open reactor for the SHPDACWL process to allow moisture to escape.
[0134] in conclusion
[0135] The high pulp density cracking leaching process is developed based on the acidic soaking water leaching process used to crack low-grade ores or concentrates. Since the traditional acid roasting water leaching process no longer requires expensive rotary kilns, HPDCWL has become a promising alternative method for cracking and leaching rare earth elements. Despite the success of the HPDCWL process with stirring during the cracking process, it has been found that the process reactor consisting of a stirred tank is subject to very harsh conditions, such as high acidity, high temperature, and high slurry viscosity. These factors may cause rapid corrosion of the material, ultimately resulting in reduced performance and increased maintenance costs. Therefore, this study aims to demonstrate the effect of modifying the HPDCWL process so that stirring is no longer used in the cracking step.
[0136] This study confirmed that agitation is not necessary during the cracking step of the process. Metal recovery was better in this static process where agitation was not required. By adding more acid, the process has the potential to achieve over 90% TREE recovery. The study concluded the following for the process variables: - By calculating the overall economic benefits, the amount of acid added in the cracking step can be reasonably increased to maximize the recovery of rare earth elements; - This study discovered a hidden factor in process control, namely that the pyrolysis process works better when the pyrolysis solid residue is dry and not wet; - for the feed sample, the lysis time is controlled to be between about 4 hours and about 6 hours, wherein the duration is selected to be long enough to produce a dry solid residue from the lysis step; - Leaching performance is affected by the success of the cracking step, but in general, cracking success requires a shorter leaching duration (1.5 hours) and ambient temperature, with water usage during leaching being effective at least in the pulp density range of about 20% to about 14%.
[0137] References -Bauer,D.,Diamond,D.,Li,J.,Sandalow,D.,Telleen,P.,&Wanner,B.(2011). Critical Materials Strategy.USDepartment of Energy. -Demol,J.,&Senanayake,G.(2018).Sulfuric acid baking and leaching ofrare earth elements,thorium and phosphate from a monazite concentrate:Effect ofbake temperature from 200to 800℃.Hydrometallurgy,179,254-267. -Qi,D.(2018).Hydrometallurgy of rare earths:Extraction andseparation.Cambridge: Elsevier. -Sadri,F.,Nazari,A.,&Ghahreman,A.(2017).Areview on the cracking,baking andleaching processes of rare earth element concentrates.Journal ofRare Earths,35(8),739-752. -Kumari,A.,Panda,R.,Jha,M.K.,Jumar,J.R.,and Lee,J.Y.,2015.Processdevelopment to recover rare earth metals from monazite mineral:Areview.MineralsEngineering,70:102-115. -McGill,I.,1997.“Part Ten:Rare Earth Metals”,In:Habashi,F.(ed.)Handbook ofExtractive Metallurgy Volume III.Federal Republic of Germany:Wiley-VCH,1693-1741pp. -Verbaan,N.,Bradley,K.,Brown,J.,and Mackie,S.,2015.Areviewofhydrometallurgical flowsheets considered in current REE projects.In:Simandl,G.J. and Neetz,M.,(Eds.),Symposium on strategic and critical materialsproceedings, November 13-14,2015,Victoria British Columbia Ministry of Energy and Mines, British Columbia Geological Survey Paper 2015-3.147-162.
[0138] Exemplary embodiments
[0139] The following are non-limiting exemplary embodiments of the present invention: 1. A method for extracting rare earth elements from a solid feed, the method comprising: a. Grinding the solid feed; b. mixing the ground solid feed with a strong acid and water to form a slurry or mud having a solid-liquid slurry density of at least 33%, and pyrolyzing the slurry or mud in a reactor at a temperature of about 30° C. to about 300° C. for about 30 minutes to about 6 hours; and c. Leaching the product of step (b) with an aqueous leaching solution to obtain a leachate containing rare earth elements. 2. A method for extracting rare earth elements from a solid feed, the method comprising: a. Grinding the solid feed; b. mixing the ground solid feed with a strong acid and water to form a slurry having a solid-liquid slurry density of at least 33%, and stirring the slurry in a reactor at a temperature of about 30° C. to about 300° C. for about 30 minutes to about 6 hours; as well as c. leaching the slurry with an aqueous leaching solution to obtain a leachate containing rare earth elements. 3. The method of claim 1, wherein the lysis of the slurry or mud in step (b) is a static step, wherein the slurry or mud is not stirred or agitated after mixing. 4. The method according to any one of embodiments 1 to 3, wherein the strong acid is HNO3, HCl or H2SO4. 5. The method according to embodiment 4, wherein the strong acid is HNO3 or H2SO4. 6. The method according to any one of embodiments 1 to 5, wherein the solid-liquid slurry density in step (b) is about 33% to about 90%, or about 50% to about 80%, or about 55% to about 75%, or about 65% to about 80%, or about 70% to about 75%. 7. The method according to any one of embodiments 1 to 6, wherein the temperature of step (b) is from about 30°C to about 200°C, or from about 30°C to about 100°C. 8. The method of embodiment 7, wherein the temperature of step (b) is from about 85°C to about 100°C. 9. The method according to any one of embodiments 1 to 8, wherein the aqueous leaching solution is water or a rare earth element-depleted acidic solution. 10. The method of any one of embodiments 1 to 9, wherein the duration of leaching is from about 1 hour to about 10 hours, or from about 1 hour to about 5 hours, or from about 2 hours to about 5 hours, or about 2.5 hours. 11. The method according to any one of embodiments 1 to 10, wherein leaching is carried out at a temperature or temperature range of about 20°C to about 100°C, such as about 20°C to about 90°C, about 20°C to about 50°C. 12. A system for extracting rare earth elements from a solid feed containing rare earth elements, the system comprising: a. a grinding and / or milling device for grinding the solid feed to produce a ground solid feed; b. a cleavage reactor having a ground solid feed inlet, a strong acid inlet, a water inlet and a mixed slurry outlet fluidly connected to the grinding and / or milling device, wherein the ground solid feed is received in the cleavage reactor and mixed with the strong acid and water by an agitator arranged in the reactor to form a slurry having a solid-liquid slurry density of at least 33%; c. a means for heating the reactor to a temperature of from about 30°C to about 300°C for from about 30 minutes to about 6 hours; and d. A leaching device comprising a leaching chamber having a mixed slurry inlet fluidly connected to the mixed slurry outlet of the reactor, an aqueous leach solution inlet and a leach slurry outlet. 13. The system of embodiment 12, wherein the strong acid is HNO3, HCl, or H2SO4. 14. The system of embodiment 13, wherein the strong acid is HNO3 or H2SO4. 15. The system of any one of embodiments 12 to 14, wherein the solid-liquid slurry density of the slurry in the cleavage reactor is about 33% to about 90%, or about 50% to about 80%, or about 55% to about 75%, or about 70%. to about 85%, or from about 70% to about 75%. 16. The system according to any one of embodiments 12 to 15, wherein the cleavage reactor is heated to about 30°C to a temperature of about 200°C, or a temperature of about 30°C to about 100°C. 17. The system of any one of embodiments 12 to 16, wherein the aqueous leach solution inlet provides water or a rare earth element-depleted acidic solution into the leaching chamber. 18. The system of any one of embodiments 12 to 17, further comprising means for heating the leaching chamber to about 20°C to about 100°C, about 20°C to about 90°C, or about 20°C to about 50°C. 19. The system of any one of embodiments 12 to 18, further comprising a control device for controlling the device for heating the cracking reactor. 20. The system of any one of embodiments 12 to 19, further comprising a monitoring device for monitoring slurry properties in the cleavage reactor during the cleavage reaction.
[0140] The present invention is described above, and it is obvious that the present invention can be modified in many ways. Such changes should not be regarded as departing from the spirit and scope of the present invention, and it is obvious to those skilled in the art that all such modifications are intended to be included within the scope of the following claims.
[0141] All publications, patents, and patent applications mentioned in this specification are indicative of the levels of skill of those skilled in the art to which this invention pertains and are incorporated herein by reference as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference.
Claims
1. A method for extracting rare earth elements (REE) from a solid feed, the method comprising: (a) grinding a solid feed; (b) mixing a ground solid feed with a strong acid and water to form a slurry or mud having a solid-liquid slurry density of at least 33%, and pyrolyzing the slurry or mud in a reactor at a temperature of about 30° C. to about 300° C. for about 30 minutes to about 6 hours; as well as (c) leaching the product of step (b) with an aqueous leaching solution to obtain a leachate containing rare earth elements.
2. The method of claim 1, wherein the lysis of the slurry or mud in step (b) is a static step; Alternatively, during the cleavage process in step (b), the slurry or slurry is stirred in the reactor.
3. The method according to claim 1, wherein the strong acid is HNO3, HCl or H2SO4.
4. The method according to claim 2, wherein the strong acid is HNO3 or H2SO4.
5. The method of claim 1, wherein the solid-liquid slurry in step (b) has a density of about 33% to about 90%, or about 50% to about 80%, or about 65% to about 80%, or about 55% to about 75%, or about 70% to about 75%.
6. The method of claim 1, wherein the temperature of step (b) is from about 30°C to about 200°C, or from about 30°C to about 100°C.
7. The method of claim 6, wherein the temperature of step (b) is from about 85°C to about 100°C.
8. The method of claim 1, wherein the aqueous leaching solution is water or an acidic solution depleted in rare earth elements.
9. The method of claim 1, wherein the duration of leaching is from about 1 hour to about 10 hours, or from about 1 hour to about 5 hours, or from about 2 hours to about 5 hours, or about 2.5 hours.
10. The method of claim 1, wherein leaching is carried out at a temperature or a temperature range of about 20°C to about 100°C, about 20°C to about 90°C, about 20°C to about 50°C.
11. A system for extracting rare earth elements (REEs) from a solid feed containing rare earth elements, the system comprising: (a) a grinding and / or milling device for grinding a solid feed material to produce a ground solid feed material; (b) a cleavage reactor having a ground solid feed inlet, a strong acid inlet, a water inlet and a mixed slurry outlet fluidly connected to the grinding and / or milling device, wherein the ground solid feed is received in the cleavage reactor and mixed with the strong acid and water by an agitator arranged in the reactor to form a slurry having a solid-liquid slurry density of at least 33%; (c) means for heating the reactor to a temperature of about 30° C. to about 300° C. for about 30 minutes to about 6 hours; as well as (d) a leaching device comprising a leaching chamber having a mixed slurry inlet fluidly connected to the mixed slurry outlet of the reactor, an aqueous leach solution inlet and a leach slurry outlet.
12. The system of claim 11, wherein the strong acid is HNO3, HCl, or H2SO4.
13. The system of claim 12, wherein the strong acid is HNO3 or H2SO4.
14. The system of claim 11, wherein the solid-liquid slurry density of the slurry in the cleavage reactor is from about 33% to about 90%, or from about 50% to about 80%, or from about 55% to about 75%, or from about 70% to about 85%, or from about 70% to about 75%.
15. The system of claim 11, wherein the cleavage reactor is heated to about 30°C to about 200°C, or about 30°C to about 100°C.
16. The system of claim 11, wherein the aqueous leach solution inlet provides water or a rare earth element-depleted acidic solution into the leach chamber.
17. The method of claim 11, wherein the system further comprises means for heating the leach chamber to about 20°C to about 100°C, about 20°C to about 90°C, or about 20°C to about 50°C.